ANALISIS PELAKSANAAN PROGRAM KESELAMATAN PASIEN DI UNIT RAWAT INAP RS WAVA HUSADA KABUPATEN MALANG - Anggia Nuaristia Dewi; Septo Pawelas Arso; Eka Yunila Fatmasari (Jurnal Kesehatan Masyarakat (Undip), 2019)
The issue about patient safety is one of important issues in health service. Wava Husada Hospital is a type B provides service.The incidence of patient safety that occurs at Wava Husada Hospital increases from 2017 to 2018. In 2018 there were 48 incidents from January to July. The purpose of this study is to analyze the implementation of patient safety goals in the Hospitalization Unit at Wava Husada Hospital. This is a qualitative research with description approach. The main informants are six nurses executive in the hospitalization unit at Wava Husada Hospital. The result showed the implementation of appropriate certainty-location, right-procedure, right surgery is in compliance with service operational standards owned while the execution patient identification, the implementation of effective communication, the implementation of security enhancement drugs need to be aware, the implementation of the reduction of the risk of infection and the implementation of risk reduction in patients fell not in accordance with the service operational standards owned.   Some infrastructure facilities that were not immediately repaired or replaced and the lack of awareness and commitment of nurses to provide appropriate services became a major problem in the services provided by Wava Husada Hospital.The suggestion for Wava Husada Hospital is to increase the commitment of leaders through the provision of periodic training and selecting champion units in accordance with predetermined terms and criteria. And provide media reminders in each unit.